2021
DOI: 10.1186/s10020-021-00414-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect and mechanism of Jiao-tai-wan in the treatment of diabetes mellitus with depression based on network pharmacology and experimental analysis

Abstract: Background The incidence of diabetes mellitus (DM) and depression is increasing year by year around the world, bringing a serious burden to patients and their families. Jiao-tai-wan (JTW), a well-known traditional Chinese medicine (TCM), has been approved to have hypoglycemic and antidepressant effects, respectively, but whether JTW has such dual effects and its potential mechanisms is still unknown. This study is to evaluate the dual therapeutic effects of JTW on chronic restraint stress (CRS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 102 publications
0
15
0
Order By: Relevance
“…The cure is directed to reduce depression in individuals with diabetes to help them socialize, thus improving their health status. TCMs have been reported to cure many ailments, including diabetes‐associated depressive symptoms 39,40 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The cure is directed to reduce depression in individuals with diabetes to help them socialize, thus improving their health status. TCMs have been reported to cure many ailments, including diabetes‐associated depressive symptoms 39,40 …”
Section: Discussionmentioning
confidence: 99%
“…TCMs have been reported to cure many ailments, including diabetes-associated depressive symptoms. 39,40 Thus, this study was designed to formulate R-SMS that comprises four bioactive components, namely Puerarin, Ginsenosides, Schizandrin, and Ruscogenin. 41 All the components of R-SMS have been shown to be neuroprotective, especially antidepressant activity among chronic unpredictable mild stress mouse models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 The insulin receptor substrate 1/phosphoinositide 3-kinase/protein kinase B insulin receptor substrate 1/glucose transporter type 4 (IRS-1/PI3K/AKT/GLUT4) signaling pathway is a crucial downstream molecular pathway of insulin, governing glucose metabolism, IR, and neuronal survival. 11,12 Notably, studies have indicated that ApoE4 can impair cerebral insulin signaling compared to ApoE3, resulting in reduced responsiveness to both peripheral and cerebral insulin signaling upon insulin administration. 13 Hence, examining alterations in the insulin signaling pathway can provide valuable insights into the impact of interventions on the IR status and brain function in the context of the ApoE genotype.…”
Section: Introductionmentioning
confidence: 99%